Synthesis of surface-modified porous polysulfides from soybean oil by inverse vulcanization and its sorption behavior for Pb(II), Cu(II), and Cr(III) - Lyu, Shiqi; Abidin, Zurina Zainal; Yaw, Thomas Choong Shean; Resul, Mohamad Faiz Mukhtar Gunam (Springer, 2024)
Guided by efficient utilization of natural plant oil and sulfur as low-cost sorbents, it is desired to tailor the porosity and composition of polysulfides to achieve their optimal applications in the management of aquatic heavy metal pollution. In this study, polysulfides derived from soybean oil and sulfur (PSSs) with improved porosity (10.2–22.9 m2/g) and surface oxygen content (3.1–7.0 wt.%) were prepared with respect to reaction time of 60 min, reaction temperature of 170 °C, and mass ratios of sulfur/soybean oil/NaCl/sodium citrate of 1:1:3:2. The sorption behaviors of PSSs under various hydrochemical conditions such as contact time, pH, ionic strength, coexisting cations and anions, temperature were systematically investigated. PSSs presented a fast sorption kinetic (5.0 h) and obviously improved maximum sorption capacities for Pb(II) (180.5 mg/g), Cu(II) (49.4 mg/g), and Cr(III) (37.0 mg/g) at pH 5.0 and T 298 K, in comparison with polymers made without NaCl/sodium citrate. This study provided a valuable reference for the facile preparation of functional polysulfides as well as a meaningful option for the removal of aquatic heavy metals. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.